2012
DOI: 10.1136/bmjspcare-2012-000277
|View full text |Cite
|
Sign up to set email alerts
|

Late effects and healthcare needs of survivors of allogeneic stem cell transplantation: a qualitative study

Abstract: Purpose This qualitative study of survivors of allogeneic stem cell transplantation (SCT) for hematologic malignancy explored attitudes about late effects of therapy, healthcare issues and information needs. Methods We conducted 12 in-depth cognitive interviews and 3 focus groups of patients who had previously had SCT and were without recurrence of their primary disease. We used grounded theory methods, where themes emerged from consensus between co-coders. Health-related quality of life was assessed with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…However, the patient experience of these clinics and their subjective impact on patients requires consideration. In previous qualitative work in the U.S., survivors of HSCT have expressed a preference for care from specialists, feeling that other providers did not understand the complexities of their condition [ 13 ]. Furthermore, U.S. focus groups identified concerns whereby patients felt let-down and ‘left on their own’ to deal with their cGVHD care post-HSCT [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the patient experience of these clinics and their subjective impact on patients requires consideration. In previous qualitative work in the U.S., survivors of HSCT have expressed a preference for care from specialists, feeling that other providers did not understand the complexities of their condition [ 13 ]. Furthermore, U.S. focus groups identified concerns whereby patients felt let-down and ‘left on their own’ to deal with their cGVHD care post-HSCT [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Management of these patients relies on using validated and sensitive patient-reported outcome instruments (PROMs), focusing on QOL and symptom burden, to better monitor disease progression and treatment response. However, our recent systematic review of PROMs in this patient group revealed that there are limited qualitative data in the bone marrow transplant literature exploring QOL themes [7], with only 11 qualitative articles focussing on GVHD [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our study results, it is clear that nurses may contribute to improving patients’ quality of life by determining the physiological problems in the patients with autologous and allegeneic stem cell transplantation and by showing them constructive ways in which to cope with their health issues. [620212223]…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of BMT survivors showed that patients continue to seek information from a variety of sources, including health care providers and publications, with a preference for online information [37]. Internet-based programs provide broad education delivery reaching large numbers of transplantation recipients; however, broad-scale information can also be a paradoxical barrier to education delivery, often failing to target individual needs of BMT recipients [19] and cancer patients [38,39].…”
Section: Education Processmentioning
confidence: 99%